Glitter When You Jump: Celebrating the Seven Age of Woman - Waters, Fiona (Macmillan Publishers Ltd, 1996)
This book is a collection of peoms celebrating the Seven Ages of Woman$1! =s
Keywords: Literature; Non-Fiction; Poems